Political Tafsīr and the Construction of Governance Discourse: Qur'anic Hermeneutics in Raja Ali Haji's Tsamarat al-Muhimmah - Ridho Yoni Aprilianto; Novizal Wendry; Ahmad Taufik Hidayat (Mashdar: Jurnal Studi Al-Qur'an dan Hadis, 2025)
Qur’anic interpretation is inseparable from the historical, intellectual, and socio-political contexts of its interpreter. In the nineteenth-century Malay world, the Qur’an functioned not only as a religious text but also as a source of legitimacy for political authority, legal institutions, and systems of governance. Yet the role of Qur’anic interpretation in shaping Malay political thought remains underexplored. This article examines Raja Ali Haji’s Tsamarat al-Muhimmah to analyse its interpretive method, epistemological foundations, and forms of Qur’anic reception within the Riau-Lingga Sultanate. This qualitative library-based study employs Qur’anic reception theory and social construction theory within a Critical Discourse Analysis framework. The findings indicate that Raja Ali Haji adopted a predominantly taḥlīlī approach grounded in ra’y (reasoned interpretation), characterised by a socio-literary orientation and sensitivity to local political realities. His interpretations were shaped by three interrelated influences: his experience as a royal adviser, a religious worldview informed by the Khalidiyyah-Naqshbandiyyah Sufi tradition, and engagement with al-Ghazālī’s Naṣīḥat al-Mulūk. These influences enabled him to formulate a Qur’an-based vision of governance that integrated political authority, legal order, and ethical leadership. The study further demonstrates that Qur’anic reception in Tsamarat al-Muhimmah is predominantly performative-functional. Qur’anic verses are employed as normative foundations for political, legal, and statecraft discourses while simultaneously informing regulations and socio-political practices. By showing how scriptural interpretation was transformed into mechanisms of governance, this article highlights the Qur’an’s role as a source of knowledge production, political legitimacy, and social transformation in the nineteenth-century Malay world. The findings contribute to broader discussions on the relationship between scripture, authority, and political culture in Islamic societies.